Biogeographic history of the endangered dwarf buffalo, subgenus Anoa (Bovidae: Bubalus quarlesi and Bubalus depressicornis): a perspective based on mitochondrial DNA phylogeny - Dwi Sendi Priyono; Dedy Duryadi Solihin; Achmad Farajallah; Bambang Purwantara (Evolutionary Systematics)
The Anoa, including the Mountain Anoa (Bubalus quarlesi) and the Lowland Anoa (Bubalus depressicornis) according to current taxonomy, are endangered bovid species endemic to the tropical island of Sulawesi. They are grouped in their own subgenus Anoa. The historical biogeography and phylogeny of this subgenus have not been well characterized. There are two hypotheses describing the colonization routes of large mammals in Southeast Asia: land-bridges and insular route. The present study aimed to understand the molecular phylogeny and test the historical colonization route of Anoa. A total of 71 mitochondrial DNA (cyt b gene and control region) sequence datasets from Anoa and other related species were analyzed. Molecular phylogeny reconstruction was done using a Bayesian inference model. Calibration points were used to estimate divergence time in Anoa based on a Bayesian phylogeny tree. Estimation of ancestral areas in Anoa ancestors using Reconstruct Ancestral State in Phylogenies was carried out to test the Anoa colonization route. The phylogenetic tree revealed the existence of two groups of Anoa, lowland and mountain Anoa, which diverged during the Middle Pleistocene 1.42 Mya (highest posterior density interval: 1.14–1.71 Mya). The Sundaland area is the most probable (P > 0.7) ancestral area for the Bubalus spp. in the Indonesian archipelago. The most probable Anoa colonization route appears to be through land-bridges, which geological records indicate formed between Sundaland and Sulawesi during the Pleistocene.